Moderate fermentation contributes to the formation of typical aroma and good organoleptic properties: A study based on different brands of Chouguiyu. (December 2021) - Yang, Zhaoxia; Wu, Ruohan; Wei, Xiaohan; Zhang, Zuoli; Wang, Wenqing; Liu, Aoxue; Yang, Jing; Ji, Chaofan; Liang, Huipeng; Zhang, Sufang; Lin, Xinping
Abstract: Little is known about the relationship between the chemical and microbial properties of Chouguiyu, a traditional Chinese fermented fish with unique aroma and plentiful taste. Therefore, we explored this relationship by determining the bacterial and fungal distribution of 14 brands of Chouguiyu . The distribution of microorganism and their effect on product quality, such as volatile flavor compounds (VFCs), free amino acids (FAA), physicochemical features and organoleptic properties were evaluated. Five VFCs (2-ethyl-1-hexanol, eucalyptol, 1-octen-3-ol, nonanal and indole) and three FAAs (Glu, Vla and Ala) were considered as core components. LAB ( Vagococcus and Lactococcus ) were found to contribute greatly to critical aroma formation and inhibition of TVB-N, leading to a moderate fermentation and good quality. While excessive increases in TVB-N, VFCs and FAA contents were found to be related with Psychrilyobacter and Fusobacterium, leading to poor organoleptic properties. The addition of Sufu to these products may be associated with the accelerating the fermentation process. Moderate fermentation with LAB is beneficial to typical aroma and good organoleptic properties, while excessive fermentation related with Psychrilyobacter and Fusobacterium may lead to overpowering flavors and lowered organoleptic properties. Highlights: Bacterial and fungi diversities were firstly studied among different Chouguiyu. Psychrilyobacter and Fusobacterium might be related with overfermentation. Moderate fermentation lead to typical aroma and good organoleptic properties.